A physico-chemical investigation of the volatile oil of Citrus nobilis Lour. (small type variety) (Family Rutaceae) - Follosco, Estrella P.; Castillo, Amorita V.; Bernal-Santos, Rizalina M. (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1977)
The fresh rind of the ripe fruit of Citrus nobilis Lour. It is considered as the Batangas mandarin with small fruits variety. By Clevenger method of distillation of the rind, it contained 10.3-12% of volatile oil. The physical and chemical properties of the oil were subjected to thin layer chromatography, column chromatography and by the use of UV spectrophotometer.
The oil was tested with different solvent systems and showed best solubility in 95% benzene and 5% acetone. The average specific gravity was found to be 0.8412, the average refractive index at 26°C was 1.4700, the average optical rotational determination gave +91.709. the UV spectrophotometry of the fraction of oil compared to the standard showed a strong resemblance with that of d-limonene and pinene as its major constituent and some others which were not isolated.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, 1977.
Keywords: Essences and essential oils; Mandarin orange